Sistem Pakar Dalam Mendiagnosa Jenis Perawatan Kulit Wajah Menggunakan Metode Certainty Factor (Klinik House Of Ristra) - Efrianti Marsinta; Dewi Suranti; Indra Kanedi (UNIVED Press, 2023)
Abstract_The skin is the outermost organ of the body that lines the human body. The skin makes up 15% of the total body weight. On the outer surface of the skin there are pores (cavities) through which sweat comes out. The skin has many functions, including protecting the body, as a means of touch or communication, and as a means of controlling temperature. To do skin care requires sufficient knowledge. Before carrying out skin care, determining the type of facial skin is very necessary because the determination of skin care must be adjusted to the type of facial skin. The role of a skin specialist is very necessary in determining the type of facial skin care according to skin type. The limited number of dermatologists and doctor's hours of practice, very long queues and long distances are obstacles that are often experienced by most women who seek treatment at beauty clinics. Therefore a tool is designed using an expert system to diagnose facial skin types early. This expert system was designed using the PHP Programming Language and MySQL database by implementing the Certainty Factor Method. The expert system created can make it easy for users to consult about facial skin types online. From the results of tests carried out by the certainty factor method, it can be used as a solution in using an expert system to diagnose this type of facial skin care. In applying the certainty factor method, it can provide a percentage of the level of confidence in a disease. So that users can make this expert system as an application that can provide assistance in facial care.